Ir, vir e resistir: a mobilidade do trabalho camponês em Itabaiana/SE - Costa, Juliana Lima da (2021)
The process circumscribed to the emptying of the countryside, in the midst of the development of the capitalism as a world trend, occurs in Brazil starting especially in the 1930’s. During this period, the State intensified its action in order to get a bigger insertion of the country in the reproductive dynamic of the capital, which resulted in deep transformations in work and production relationships in the countryside and in the city. The basis of the economy, until then agrarianexporting, becomes, in its conception, urban-industrial, although significant fractions of the bourgeoisie, from agrarian origin, remain linked to economic, political and social purposes that considered industrial activity as a perspective to overcome the delay. Within the spatial dynamics, there is a progressive reduction of the population from the countryside with the correlated and accelerated urbanization process. It is remarkable that, especially starting in the 1960’s, there’s an increasingly intense labor mobility. This mobility, understood as a phenomenon that promotes the spatial, sectoral and professional displacement of the worker, with the goal of the Capital to explore its workforce and to accumulate economic surplus, materializes its condition of subjection to the Capital. Based on this assumption, the goal of the research is to analyze the mobility of the peasant labor in Itabaiana, given the growing number of peasants who live in the city but continue to work in their small properties. It was sought to understand whether this fact is part of the process of structural unemployment that subordinates the worker or it is configured, as a way of resistance of the peasants to continuing to reproduce their way of life on the land, even residing in the city. From the dialectical historical materialism interpretation method, as well as from the methodological procedures proper to a qualitative research, such as interviews and questionnaire application, it was possible to analyze the singularities existed in the context of the expansion of capitalism in the countryside. It was observed that the reasons that led the peasants to migrate to the city are diverse, given that the peasantate is a non-homogeneous class with its differentiations. But, above all, it was highlighted the effective absence of the land ownership, made impossible by the increase in the value of the land, resulting from the process of valorization and speculation. In the area investigated, inheritance and free lending predominate as a way of land ownership. Thus, the land is fragmented, and with the reduced size, oftentimes it ends up making it impossible to hold the whole family, which results in the going to the city. Therefore, living in the city and working in the countryside has been configured as a way for the peasants to continue holding themselves in the midst of the logic of the Capital that subordinates it by appropriating the income of the land as a way of accumulation, making this natural good a form of fictitious capital.